Promotion Strategy through the Use of Instagram in Public Library of Depok City during Pandemic COVID-19 - Andrian Prayudho; Muhammad Azwar (Syarif Hidayatullah State Islamic University of Jakarta, INDONESIA, 2022)
Library promotion is important, especially during a pandemic like this. This study aims to determine the use of Instagram as a means of promotional activities carried out by the Depok City Public Library manager during the COVID-19 pandemic. The research method used is a descriptive qualitative method with a phenomenological approach. Data collection techniques are collected through interviews, observations, and literature studies (documentation). The results showed that the strategy carried out by the Depok City Public Library through Instagram social media was to embrace the reading garden community around Depok City, upload content in the form of events and activities carried out by the Depok City Public Library, as well as cooperation with schools in Depok City. To improve the quality of promotion through Instagram, it is necessary to support the leadership on various kinds of existing problems, including the first, namely the policy on the certainty of the use of language (formal / non-formal). The second is the policy toward the procurement of experts in the field of graphic design. Furthermore, the third is the formulation of regulations to guide the implementation of all activities related to promotion using Instagram